PENGARUH STRATEGI PEMASARAN POP-UP STORE, CUSTOMER EXPERIENCE DAN HARGA TERHADAP VISIT INTENTION KONSUMEN - Michelle Henny Limbono; Beatrix Adelaide Herijanto; Sri Nathasya Br Sitepu; Irantha Hendrika Kenang; Gladys Greselda Gosal (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to analyze the influence of pop-up store marketing strategies, customer experience, and prices on consumer visit intent at La Brisa Sunday Market Bali. Using the framework of Theory of Planned Behavior (TPB), this study examines the relationship between attitudes, subjective norms, and behavioral control on the intention to visit. Data was obtained through a questionnaire to 385 respondents, the majority of whom were domestic tourists aged 20–44 years. The results of the regression analysis showed that the three independent variables had a significant effect on visit intention, with customer experience as the most dominant factor (t = 9,449), followed by price (t = 9,299) and pop-up store strategy (t = 5,518). Key indicators that influence visitor intent include social media recognition, competitive pricing, and market path design. These findings provide strategic implications for MSMEs and market managers to improve visual elements, cultural experiences, and the integration of cashless payment systems in the development of pop-up market-based destinations.